Tumultos y resistencia indígena en Mauretania Tingitana (siglo II) - Gozalves Cravioto, Enrique (Gerión. Revista de Historia Antigua, 2002)
The work studies the testimonies referred to tumulta and raisings in the Roman province in the century II. These indigenous revolts were not successive episodes of the same confrontation but conflicts developed in each case by different ethnic groups.